Growing Elementary School Students’ Collaboration Skills through the Project-Based Learning Model - Pramusinta, Yulia; Dewi, Larasati Permata (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study seeks to examine the effect of the Project-Based Learning Model (PJBL) model on enhancing the collaboration skills of 3rd-grade students at Madrasah Ibtidaiyah Ma’arif Nahdlatul Ulama Sungegeneng, particularly in Arts and Culture subjects. It employed a quantitative pre-experimental approach using a one-group pretest-posttest design. Data were collected through collaboration questionnaires, teaching modules, interviews, observations, and documentation. The participants consisted of 34 3rd-grade students of Madrasah Ibtidaiyah Ma’arif Nahdlatul Ulama Sungegeneng. The findings revealed that the mean pre-test score was 47.29, while the mean post-test score increased to 78.85, indicating a gain of 31.56 in collaboration skills. The results of the hypothesis testing showed a p-value of 0.000, suggesting that Ha was accepted. Therefore, it can be concluded that the implementation of the PJBL model has a significant effect on students’ collaboration skills in 3rd-grade Arts and Culture subjects at Madrasah Ibtidaiyah Ma’arif Nahdlatul Ulama Sungegeneng. The implications of this study indicate that the PjBL model can serve as an effective alternative instructional strategy for enhancing elementary school students’ collaboration skills, particularly in Arts and Culture subject.